Snow [compact disc, unabridged] - Banville, John (Harlequin Audio, 2020)
Following the discovery of the corpse of a highly respected parish priest at Ballyglass House, the Co. Wexford family seat of the aristocratic, secretive Osborne family, Detective Inspector St John Strafford is called in from Dublin to investigate. Strafford faces obstruction from all angles but carries on determinedly in his pursuit of the murderer. However, as the snow continues to fall over this ever-expanding mystery, the people of Ballyglass are equally determined to keep their secrets.